PHACE SENDROMU - TAŞTAN, Yücel; ÖZGÜR, Bülent; TÜYSÜZ, Beyhan; ÇELEBİ, Ahmet and İLTER, Özdemir (Cerrahpaşa Medical Journal, 2014)
Background.- Hemangiomas are the benign tumor of vascular endothelium. Unlike vascular malformations, they are rarely associated with structural abnormalities. A new neurocutaneous syndrome (PHACE syndrome) has been recently described in cases with large facial hemangioma associated with structural systemic abnormalities. Observation.- We report an infant with large facial hemangioma associated with posterior fossa brain malformations ( Dandy-Walker malformation and left cerebellar hemisphere hypoplasia), internal carotid artery anomalies, silent patent ductus arteriosus, strabismus and small hepatic caverneous hemangiomas. To our knowleged there was no documented case of PHECE syndrome in Turkey.